Molecular methods based detection of pathogenic mycoplasmas of chicken - Dipu M K (Department of Veterinery Microbiology, College of Veterinary and Animal Sciences, 2006)
A study was undertaken for the detection of Mycoplasma DNA from the specimens by Polymerase Chain Reaction (PCR), differentiate the three significantly pathogenic mycoplasmas of chicken namely M. gallisepticum, M. synoviae and M. iowae from the other less pathogenic ones based on the result of polymerase chain reaction. Attempts were also carried out to isolate Mycoplasma from clinical samples testing positive by polymerase chain reaction and from a few randomly selected negative samples and to comprehend the different strains of M. gallisepticum, if any, among chicken of various age groups. Out of a total of 225 birds subjected for the study 25 were found positive for the presence of avian Mycoplasma by genus-specific PCR. Thirty samples from these twenty-five birds were positive. Tracheal swabs form all these birds were positive. Fifteen isolates were obtained from these twenty five birds when the tracheal swabs were directly streaked onto BHI agar whereas when these tracheal swabs were collected in BHI broth initially and later subcultured onto BHI agar following a positive result in PCR / colour change of the broth, only 13 of them yielded colonies. Five of the isolates were found to be M. gallisepticum by MG-PCR and these were obtained upon direct inoculation of BHI agar with tracheal swabs from birds. Those samples collected in BHI broth yielded MG colonies only in two cases. Non-MG colonies were found interspersed with MG colonies in agar plates and thus the selective isolation of MG colonies must be performed prior to subculture. The utility of PBS and buffered peptone water supplemented with glycerol as transit media for clinical samples intended for PCR was evidenced. The isolates obtained were successfully lyophilized and stored at –70°C throughout the span of the study. The PCR-RFLP pattern of the obtained MG isolates revealed uniformity among the isolates. None of the samples yielded positive result in MS-PCR and MI-PCR. The sensitivity and usefulness of molecular methods based detection of pathogenic mycoplasmas of chicken over isolation techniques could be appreciated.